METHOD OF OPTIMIZATION OF OFFICE HOURS OF FONTAN MINING HOLES SUBJECT TO THE CONDITION LIMITED AND UNLIMITED DEBITS ON THE BASIS OF MODEL OF GIDROGASMECHANIC GAS LIQUID STREAMS - Бойко, Василь Степанович; Кеба, Леонід Миколайович; Лагуш, Роман Федорович; Грибовський, Роман Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The method of optimization of office hours of fontan mining holes is offered without implementation of industrial researches on the basis of construction of distribution curves of pressure along elevator pipes and characteristic curves. For the criterion of optimization the maximal debit of mining hole, which answers a maximal selection from the object of development, is taken.